Analisis Kajian Teori Pengembangan Media Diorama Tentang Kegiatan Ekonomi di Lingkungan Sekitar Pada Muatan IPS Kelas IV di Sekolah Dasar - Indrawati, Ria; Purnamasari, Iin (Pena Edukasia, 2024)
This research is motivated by the lack of interest in learning, especially in social studies subjects. Using media in teaching can assist students in the learning process. In learning, media is an essential aspect of conveying information from educators to learners. The use of media in learning will enable the concepts or subject matter studied by students to be more easily understood. In this context, diorama is chosen as a teaching media because of its ability to present information visually and comprehensively. The purpose of using diorama is to facilitate students' understanding of various economic activities that occur around them, such as agriculture, trade, or local crafts. The theoretical approach used in the development of this diorama media includes constructivist learning theory, where students are encouraged to build their own understanding through direct experience and reflection. Additionally, visual learning theory also forms the basis, as diorama provides strong visual representations to help students better understand economic concepts. The steps in developing this diorama media include identifying learning objectives, analyzing student needs, designing a diorama concept that aligns with the curriculum, as well as implementing and evaluating the use of diorama in teaching. With this approach, it is hoped that the diorama media can become an effective tool in enhancing students' understanding of relevant economic concepts within their environment.